Energy Requirements for Sustainable Olefin Production From CO2 via Electro‐ or Thermal Catalysis - Etzold, Bastian; Hungsberg, Maximilian; Ebrahim‐Moghaddam, Mahsa; Herold, Felix; Dahmen, Nicolaus; Studt, Felix (Chemical Engineering & Technology, 2025)
Direct electrochemical CO2 reduction as well as water electrolysis (WEL) combined with hydrogenation of CO2 to methanol (MeOH) and subsequent conversion to olefins are emerging as two possible pathways for sustainable olefin production. We provide an assessment of both routes such that they can be compared in terms of energy efficiency and projected costs. Through a sensitivity analysis, we identify bottlenecks and offer targets to achieve by catalysis design and engineers. At the current state, the electrocatalytic CO2 reduction has a much lower energy efficiency, requiring major improvements in the resulting overall cell potential and achieved faradaic efficiency. The MeOH route is mainly hampered by the overpotential required for WEL and the selectivity of olefin production, resulting in 50 kWh kg−1 of olefi